Effects of Subthalamic Deep Brain Stimulation With Different Frequencies in a Parkinsonian Rat Model. Issue 2 (4th September 2020) - Li, Zhimin; Guo, Yi; Bao, Xinjie; Lei, Jianfeng; Shen, Zhiwei; Wang, Xin; Li, Luming; Li, Yongning; Wang, Renzhi
Abstract: Objective: Subthalamic deep brain stimulation (STN‐DBS) could be an effective alternative treatment for patients with Parkinson's disease (PD). However, the mechanisms of deep brain stimulation (DBS) at different frequencies are still unclear. In this study, diffusion tensor imaging (DTI) was used to detect parameter changes in different regions of rat brains after DBS, and rat exercise capacity and brain tissue immunohistochemistry were evaluated. Materials and Methods: The 6‐hydroxydopamine‐induced hemi‐parkinsonian rat models were made and divided into four groups: a control group, sham group, low‐frequency group, and high‐frequency group. Low‐frequency (30 Hz) and high‐frequency (130 Hz) DBS were given to the STN in rats. First, an open‐field experiment was used to evaluate changes in exercise performance. Then, the DTI was used to measure parameter changes in the substantia nigra (SN). Finally, immunohistochemistry was used to analyze the expression of tyrosine hydroxylase (TH), NeuN, and α‐synuclein (α‐syn) in the SN in the rats. Results: There were significant differences in movement distance changes between the high‐frequency stimulation (HFS) group and low‐frequency stimulation (LFS) group, the HFS group and Ctrl group, and the Sham group and Ctrl group (all p  < 0.05) after one week of stimulation. In the HFS group, the fractional anisotropy value of the SN was significantly higher than that of the other groups ( p  < 0.05), and the apparent diffusion coefficient and radial diffusion coefficient values were significantly lower than those of the other groups ( p  < 0.01). Immunohistochemical analysis showed that the integral optical density values of SN TH staining ( p  < 0.01) and NeuN staining ( p  < 0.05) in the HFS group were both significantly higher than those in the other groups. Conclusion: STN‐HFS (130 Hz) and sham operation for one week can significantly improve the exercise performance of PD rats. The exercise performance of PD rats in LFS group (30 Hz) is worse compared with HFS group (130 Hz). HFS plays a role in neuroprotection and improvement of exercise performance of PD rats. Moreover, DTI can be used as an effective technique to assess the therapeutic effects and severity of PD.